Exploring the Impact of Frustration on Psychological Wellbeing among Flood Victims in Different Areas of Pakistan - Jamil, Bisma; Liaquat, Amna; Saleem, Javeria (Annals of Human and Social Sciences, 2025)
The objective of this study was to identify the level of frustration and its impact on psychological wellbeing among flood victims. Natural disasters, including flood is considered a core cause of psychological distress and many more mental health issues globally. Approximately, over the past two decades particularly in Pakistan, food insecurity, as a form of natural disaster, has disrupted lives and led the majority of population to the psychological anomalies. This was a quantitative study with a cross-sectional research design by using purposive sampling method, involving 414 flood victims. The findings reveal a negative and significant relationship between frustration and psychological well-being. Gender-based mean differences indicated that women reported higher frustration levels and lower psychological well-being compared to men. This is recommended to the higher authorities to launch different prevention programs to uplift the mental wellbeing of flood victims.